Jill Robert's Ambition To Get Popularity in Scream 4 Movie (20011): An Individual Psychological Approach - MULYATI, MULYATI (2012)
The major problem of this study is to elucidate the ambition of Jill Roberts reflected in Wes Craven Scream 4 movie. The objectives of the study are; to analyze the structural elements of the movie and to analyze the character of Jill Roberts based on individual psychological perspectives. This research belongs to qualitative research. The type and the data source which are used, namely primary and secondary data. The primary data source is the movie itself. The secondary data sources are taken from books and other sources which support the analysis. The method of the data collection is library research and the technique of the data analysis is descriptive analysis In analyzing the data, the writer applies two kinds of analysis. Firstly, structural analysis approach is used to analyze the elements of the movie. It consists of characterization, setting, point of view, plot, style and theme. Secondly, the individual psychological approach is used for analyzing the ambition of Jill Roberts that influences her personality. These approaches are applied in order to get the appropriate analysis and answer the problems. The writer finds that Jill Robert's ambition in material needs tend to lead her in a bad individual personality and morality.